Tea Plants With Gray Blight Have Altered Root Exudates That Recruit a Beneficial Rhizosphere Microbiome to Prime Immunity Against Aboveground Pathogen Infection - Wang, Qiaomei; Yang, Ruijuan; Peng, Wenshu; Yang, Yanmei; Ma, Xiaoling; Zhang, Wenjie; Ji, Aibing; Liu, Li; Liu, Pei; Yan, Liang; Hu, Xianqi (Frontiers in Microbiology, 2021)
Tea gray blight disease and its existing control measures have had a negative impact on the sustainable development of tea gardens. However, our knowledge of safe and effective biological control measures is limited. It is critical to explore beneficial microbial communities in the tea rhizosphere for the control of tea gray blight. In this study, we prepared conditioned soil by inoculating Pseudopestalotiopsis camelliae-sinensis on tea seedling leaves. Thereafter, we examined the growth performance and disease resistance of fresh tea seedlings grown in conditioned and control soils. Next, the rhizosphere microbial community and root exudates of tea seedlings infected by the pathogen were analyzed. In addition, we also evaluated the effects of the rhizosphere microbial community and root exudates induced by pathogens on the performance of tea seedlings. The results showed that tea seedlings grown in conditioned soil had lower disease index values and higher growth vigor. Soil microbiome analysis revealed that the fungal and bacterial communities of the rhizosphere were altered upon infection with Ps. camelliae-sinensis. Genus-level analysis showed that the abundance of the fungi Trichoderma, Penicillium, and Gliocladiopsis and the bacteria Pseudomonas, Streptomyces, Bacillus, and Burkholderia were significantly (p < 0.05) increased in the conditioned soil. Through isolation, culture, and inoculation tests, we found that most isolates from the induced microbial genera could inhibit the infection of tea gray blight pathogen and promote tea seedling growth. The results of root exudate analysis showed that infected tea seedlings exhibited significantly higher exudate levels of phenolic acids and flavonoids and lower exudate levels of amino acids and organic acids. Exogenously applied phenolic acids and flavonoids suppressed gray blight disease by regulating the rhizosphere microbial community. In summary, our findings suggest that tea plants with gray blight can recruit beneficial rhizosphere microorganisms by altering their root exudates, thereby improving the disease resistance of tea plants growing in the same soil.